(untitled) (Research, Society and Development, 2020)
Therapeutic itineraries consist of the movements triggered by individuals in choosing, evaluating and adhering (or not) to forms of treatment to solve health problems. By understanding that culture determines the type of care desired, it is intended to make nursing practice culturally based on the construction of the therapeutic itinerary of women with syphilis. The objective was to understand the therapeutic itinerary of women diagnosed with syphilis outside the puerperal pregnancy cycle. Based on the Ethnonursing method, carried out in the Municipal STD/AIDS Program in Macaé/RJ. Twenty women diagnosed with syphilis and seven health professionals participated. The data was obtained through the use of two trainers from the Cultural Care Theory, in addition to interviews. The analysis of the testimonies was based on the Ethnonursing method. The results describe the profile of the participants and two analytical categories were coded: Entry into the health care system: building the therapeutic itinerary for syphilis; and the trail of social and cultural interactions for the care of syphilis. It is argued that the therapeutic itinerary of women with syphilis is related to social and cultural issues, leading us to a responsibility as health professionals with the challenge of understanding culture and care as inseparable dimensions. It is concluded that the doubt of women in relation to the context of syphilis is significant. There was a need to discuss the problem of syphilis not only in the puerperal pregnancy cycle, and it is necessary to join efforts to advise and treat this infection in all stages of life.